Molecular and Biochemical Differences in Leaf Explants and the Implication for Regeneration Ability in Rorippa aquatica (Brassicaceae) - Rumi Amano; Risa Momoi; Emi Omata; Taiga Nakahara; Kaori Kaminoyama; Mikiko Kojima; Yumiko Takebayashi; Shuka Ikematsu; Yuki Okegawa; Tomoaki Sakamoto; Hiroyuki Kasahara; Hitoshi Sakakibara; et al. (Plants, 2020)
Plants have a high regeneration capacity and some plant species can regenerate clone plants, called plantlets, from detached vegetative organs. We previously outlined the molecular mechanisms underlying plantlet regeneration from Rorippa aquatica (Brassicaceae) leaf explants. However, the fundamental difference between the plant species that can and cannot regenerate plantlets from vegetative organs remains unclear. Here, we hypothesized that the viability of leaf explants is a key factor affecting the regeneration capacity of R. aquatica. To test this hypothesis, the viability of R. aquatica and Arabidopsis thaliana leaf explants were compared, with respect to the maintenance of photosynthetic activity, senescence, and immune response. Time-course analyses of photosynthetic activity revealed that R. aquatica leaf explants can survive longer than those of A. thaliana. Endogenous abscisic acid (ABA) and jasmonic acid (JA) were found at low levels in leaf explant of R. aquatica. Time-course transcriptome analysis of R. aquatica and A. thaliana leaf explants suggested that senescence was suppressed at the transcriptional level in R. aquatica. Application of exogenous ABA reduced the efficiency of plantlet regeneration. Overall, our results propose that in nature, plant species that can regenerate in nature can survive for a long time.